COVID-19 Pneumonia in Patients with Chronic Myocarditis (Recurrent Infectious Immune): Specifics of the Diseases Course, the Role of Basic Therapy (Part 1) - O. V. Blagova; N. V. Varionchik; M. M. Beraia; V. A. Zaidenov; E. A. Kogan; N. D. Sarkisova; A. V. Nedostup (Рациональная фармакотерапия в кардиологии)
Patients with chronic myocarditis have a high risk of an unfavorable course of the novel coronavirus disease (COVID-19) due to the ability of the SARS-Cov-2 virus to independently cause acute myocarditis, to have a direct and cytokine-mediated cytopathic effect on the myocardium, as well as immunosuppressive therapy. At the same time, the features of the interaction of chronic myocarditis and COVID-19 have not been studied. The article describes a 31-year-old patient with a 10-year history of chronic recurrent infectious-immune myocarditis, who was on long-term immunosuppressive therapy (methylprednisolone and azathioprine in the past, then hydroxychloroquine). In May 2020, a serologically confirmed COVID-19 diagnosis was made. There were risk factors for the unfavorable course of coronavirus infection: heart failure and a history of persistent atrial fibrillation, male sex. Basic therapy with hydroxychloroquine (with an increase in its dose to 800-400 mg/day), ceftriaxone, and levofloxacin was carried out. The severity of pneumonia was moderate, despite febrile fever and severe intoxication. No relapses of arrhythmias, respiratory or heart failure were observed. Minimal laboratory (some increase in anticardial antibody titers) and echocardiographic signs of exacerbation of myocarditis without an increase in troponin T levels were revealed, which quickly regressed. It can be assumed that the maintenance immunosuppressive therapy of myocarditis with hydroxychloroquine had a positive effect on the course of coronavirus pneumonia and made it possible to avoid recurrence of myocarditis. Further study of the features of the course of the pre-existing myocarditis and pneumonia in COVID-19 is necessary.